A delimitação de preço de revenda nos contratos de distribuição - Danilo Ferraz Cordova (2011)
This study aims to analyze the effects that resale price maintenance in distribution contracts may cause in the market. In the first chapter, this work explains how economic agents flow off their products to market, either in a direct way, through vertical integration, or in an indirect way, in which case the distribution contract shall be analyzed, distinguishing itself from the other sorts of contracts. The second chapter is dedicated to the vertical agreements and vertical restrictions, as well as to intra and interbrand competition and price and nonprice competition. Next, the research broaches the Economic Analysis of Law and the efficiencycriterion, according to Vilfredo Pareto, Nicholas Kaldor and J. R. Hicks. Resale price maintenance in all its species fix, minimum, maximum and suggested as well as its positive and negative possible effects will also be taken under consideration. In the last chapter, this study analyses following decisions: 1. Supreme Court of the United States ofAmerica - from Dr. Miles to Leegin cases; 2. European Commission, as well as its bloc exemption Regulations and 3. Administrative Council for Economic Defense - CADE and Judiciary Power in Brazil. After all these considerations, this research comes up to a critical overview of the Brazilian application of rules concerning resale price maintenance. This study also concludes that such a vertical restriction must not be considered per se illegal bringing up the necessity to examine its reasonableness case by case.